Pengaruh Penggunaan Selebriti Endorser Terhadap Brand Awareness Akun Instagram @georgiosstore Di Kalangan Siswi SMA Negeri 1 Denpasar - Mentari Pramesti, Ni Nyoman Tri; Pascarani, Ni Nyoman Dewi; Sugiarica Joni, I Dewa Ayu (E-Jurnal Medium; Vol 1 No 1 (2017), 2017)
Nowadays, online media is very effective to advertise goods and services, one of online media is Instagram. Marketers have to be more creative in creating advertisements. One of the strategies to advertise in online media is by using celebrity endorser. This study aims to determine the influence of celebrity endorser towards the establishment of brand awareness on @georgiosstore’s Instagram account among female students at SMAN 1 Denpasar. This research used quantitative approach in the form of explanation which conducted through survey. The data was collected by giving questionnaires to the sample of 256 respondents from female students of SMAN 1 Denpasar. This research was conducted by using non probability sampling technique and purposive sampling method. Indicators of this study were tested using validity test and reliability test. The hypotheses were tested using simple linear regression analysis. This study resulted on the regression coefficient of celebrity endorser (X) is 0,430 (positive) with significance level 0.000 smaller than ? = 0.05, it shows that there is positive influence of celebrity endorser towards the establishment of brand awareness among female students of SMAN 1 Denpasar. Keywords: Brand Awareness, Celebrity Endorser, Instagram